Management of Traumatic Perineal Degloving Injury: A Case Series - CY, Lee; Syazwan, Abu; Omar, Syed; Anuar, Syahril; Munjih, Islah; Nazli, Mohd; Ghazali, Hamid (IIUM Medical Journal Malaysia, 2019)
Degloving injury is severe and commonly results from a huge rotational force which avulses the skin and subcutaneous tissue from its underlying fascia. This injury is associated with high morbidity and mortality if mismanaged. Perineal degloving injury commonly associated with urethral injury which can be further classified into anterior and posterior urethral injury. This study retrospectively evaluated management of traumatic perineal degloving injury compared to standard approach. A total of 3 cases of open perineal degloving injuries been identified and was managed at our centre at the year 2017. 2 cases of degloving wound of scrotum and one case of crush perineal injury with transected posterior urethral were included. We reviewed methods of management and clinical outcomes of these patients. All patients promptly underwent wound debridement and surgical repair after immediate diagnosis and resuscitation. Suprapubic insertion of catheter is crucial in managing the urethral injury. The case of crush perineal injury with transected urethral treated with operation primary urethral anastomosis, de-functioning of stoma and external fixation of pelvis. Unfortunately, this case was complicated with rupture at anastomotic urethral site after a traumatic CBD insertion during his hospitalization and he was treated conservatively with CBD. All patients did well clinically with their wounds healed well. We showed a multidisciplinary team approach consisting of colorectal surgeon, urologist, orthopaedics surgeon and plastic surgeon, together with prompt diagnosis provides the best outcome were for the treatment of open perineal degloving injury.